The enantioselective total synthesis of (-)-hyperolactone C and related spirolactone analogues using a diverted metallocarbenoid O-H insertion strategy - Whymark, Kyran (2025)
This thesis outlines and details the development of synthetic methodology achieving the enantioselective total synthesis of (-)-hyperolactone C, privileged spirolactone analogues and their related novel derivatives. The research described herein provides an elegant, accessible route to the particularly synthetically challenging spirocyclic hyperolactone topology, utilising a diverted metallocarbenoid O-H insertion transformation to enable the stereospecific assembly of densely functionalised spirolactones, from α-diazolactone and β-hydroxyketone precursors in a single step process. Chapter One introduces the hyperolactone natural product series, summarises previously reported research employed to synthesise the secondary metabolites and provides a summary of the key methodology used to construct the vicinal quaternary stereocentres of the mutually complex biologically active spirocyclic framework. Chapter Two documents the development of efficient enantioselective syntheses of suitably selected novel hyperolactone model systems from multiple synthetic strategies, enabling the direct access to, or late-stage diversification of, various hyperolactone analogues. Chapter Three discusses a devised chiral pool approach used to obtain enantioenriched α-diazolactone intermediates that were utilised to stereospecifically construct various spirolactones that were further functionalised to complete the enantioselective synthesis of (-)-hyperolactone C, and the divergent isolation of unnatural secondary metabolite variants. This chapter also details research towards an asymmetric transformation and the synthesis of novel spiro-pyranones through a ring expansion extension of the key methodology. Chapter Four reviews key findings and accomplishments of the provided research, and presents future work required for the continued advancement of this methodology. This thesis concludes with Chapter Five providing experimental procedures and full characterisation data for all synthesised compounds discussed.